Supplementation of complex natural feed additive containing (C. militaris, probiotics and red ginseng by-product) on rumen-fermentation, growth performance and carcass characteristics in Korean native steers - Ju, Mun-Su; Jo, Yong-Ho; Kim, Yoo-Rae; Ghassemi Nejad, Jalil; Lee, Jang-Gu; Lee, Hong-Gu (Frontiers in Veterinary Science, 2024)
This study evaluated the effects of a complex natural feed additive on rumen fermentation, carcass characteristics and growth performance in Korean-native steers. In this study, in vitro and in vivo experiment were conducted. Seven different levels of complex natural feed additive (CA) were added to the buffered rumen fluid using AnkomRF gas production system for 12, 24 and 48 h. All experimental data were analyzed by mixed procedure of SAS. Total gas production increased in the CA groups, with the highest response observed in the 0.06% group at 48 h of incubation (linear, p = 0.02; quadratic, p < 0.01). Regarding rumen fermentation parameters, the total volatile fatty acid (TVFA) tended to increase in all the CA groups (p = 0.07). The concentrations of butyrate, iso-butyrate, and iso-valerate significantly increased in all treatment groups (p < 0.05). In the in vivo experiment, 23 Korean-native steers were allocated to two groups: (1) Control and (2) Treatment; control +0.07% CA (DM basis), in a randomized complete-block design and blocked by body weight (ave. body weight = 641.96 kg ± 62.51 kg, p = 0.80) and feed intake (ave. feed intake = 13.96 kg ± 0.74 kg, p = 0.08) lasted for 252 days. Average daily gain decreased in the treatment group (p < 0.01). Backfat thickness significantly decreased in the CA group (p = 0.03), whereas meat color tended to increase (p = 0.07). In conclusion, in the in vitro experiment, the inclusion of complex natural feed additive decreased methane proportion and tended to increase TVFA production, but supplementation to Korean native steers decreased average daily gain and backfat thickness.